Aberrant CYP2D6 metabolizer phenotypes do not show increased frequency in patients undergoing ECT after antidepressant therapy. Issue 10 (October 2015) - Mirzakhani, Hooman; van Dormolen, Juliët; van der Weide, Karen; Guchelaar, Henk-Jan; van Noorden, Martijn S.; Swen, Jesse
Abstract : We investigated the accumulation of aberrant CYP2D6 genotypes and predicted metabolizer phenotypes (ultrarapid metabolizer, intermediate metabolizer and poor metabolizer) potentially affecting the antidepressant treatment response in depressive patients indicated for electroconvulsive therapy (ECT) compared with patients with a single episode of depression. Seventy-six Dutch White patients with unipolar or bipolar treatment-resistant depression who underwent ECT were genotyped using the Amplichip CYP450 Test for CYP2D6 . Two hundred and eight patients with a single episode of unipolar or bipolar depression were used as controls. No difference was observed in the prevalence of CYP2D6 phenotypes (poor metabolizer, intermediate metabolizer, extensive metabolizer and ultrarapid metabolizer) between the ECT and the control patients (5.3, 38.7, 56.0 and 0.0% vs. 6.4, 51.0, 42.6 and 0.0%, respectively). The types of depression (odds ratio=0.33, P =0.018) and age (odds ratio=1.55 for a 10-year increase, P <0.001), but not CYP2D6 phenotype or activity score were associated with the response to antidepressant treatment. In conclusion, preemptive genotyping for CYP2D6 currently appears to have no clinical implications in treatment-resistant depressive patients indicated for ECT. Abstract : Supplemental Digital Content is available in the text.